2010
DOI: 10.1111/j.1439-0272.2009.00952.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Multimodal’ approach to management of prostate �biopsy pain and effects on sexual function: efficacy of levobupivacaine adjuvant to diclofenac sodium – a �prospective randomized trial

Abstract: We assessed the analgesic efficacy of levobupivacaine when administered as an adjuvant to diclofenac sodium in prostate biopsy pain management and effects of prostate biopsy on sexual function. Ninety patients underwent transrectal ultrasound (TRUS)-guided biopsy of the prostate and were randomly assigned to three groups: group D received diclofenac sodium suppository; Group L received periprostatic injection of levobupivacaine; group DL received diclofenac suppository and levobupivacaine in addition. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 20 publications
1
18
1
3
Order By: Relevance
“…When evaluating LUTS with the IPSS (mild, total score 0-7; moderate, [8][9][10][11][12][13][14][15][16][17][18][19]; and severe, 20-35) at baseline compared with the other time-points, similar results were found. The mean IPSS at baseline was 10.2.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…When evaluating LUTS with the IPSS (mild, total score 0-7; moderate, [8][9][10][11][12][13][14][15][16][17][18][19]; and severe, 20-35) at baseline compared with the other time-points, similar results were found. The mean IPSS at baseline was 10.2.…”
Section: Resultssupporting
confidence: 54%
“…The IPSS classified LUTS into three categories: mild, total score 0-7; moderate, [8][9][10][11][12][13][14][15][16][17][18][19]; and severe, 20-35. Based on the IIEF-5, ED was classified into five categories: severe, total score 5-7; moderate, 8-11; mild-to-moderate, 12-16; mild, 17-21; and no ED or normal erectile function, 22-25.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the variation in the rate of pre-biopsy ED, several studies reported statistically significant changes in the rates of mild-to-severe ED 1 month after biopsy. However, after follow-up, these changes reverted to baseline [25][26][27].…”
Section: Erectile Dysfunctionmentioning
confidence: 99%
“…Periprostatik sinir bloğunun nörovasküler demette yarattığı hematom, ödem nedeniyle daha fazla erektil fonksiyon kaybı yarattığı görüşü diğer prospektif çalışmalarla desteklenmemiştir (4,8,9). Diğer bir çalışma ağrı skorunun daha az olmasının erektil fonksiyondaki değişime etkisi olmadığını yayınlamıştır (10). Bizim çalışmamızda anestezi yöntemi olarak transrektal %2 lidokain jel masajı yapılmış olup hastaların VAS derecesi ile IIEF-5 skor değişikliği arasında anlamlı ilişki bulunamamıştır (p>0.05).…”
Section: Discussionunclassified